The Sixth Zone: Historical Roots of African Diaspora and Pan-Africanism in African Development - Başak Özoral; Billy Agwanda (Journal of Universal History Studies)
The re-emergence of Pan-African ideology in the last two decades is reflected in social, political, and economic structures found in Africa today. Pan-Africanism was the foundation upon which the struggle for African continental independence was anchored. This ideology united Africans and other individuals of African descent under a continental ideology that created a domain for support, cooperation and understanding. Today, Pan-African ideology has become a pull factor for the African diaspora to contribute to African development initiatives. By tracing the historical emergence of African diaspora and Pan-Africanism in Africa, this article argues that Pan-African ideology and the experiences of African diaspora has influenced increased contributions of African diaspora to development. Using explanatory methodology, this article adopts an in-depth analysis of historical accounts of the emergence of African diaspora to examine how the African diaspora has emerged as a strong pillar of development.